797. BULBOPHYLLUM AMBROSIA. (December 2014) - Gale, Stephan W.; Kumar, Pankaj; Fischer, Gunter A.
Summary The epiphytic orchid Bulbophyllum ambrosia bears solitary, sweet‐smelling, nectariferous flowers that attract honeybees in considerable numbers, but it is self‐incompatible, making fruit‐set in the wild infrequent. Even so, the species is relatively abundant throughout its range in Asia. The species is described and illustrated and its taxonomic history, ecology and cultivation are discussed.